Visitors’ Knowledge, Awareness, and Perception (KAP) of Climate Change in Mashar National Park, Hail-Saudi Arabia - Said, M. A. (Engineering, Technology & Applied Science Research, 2022)
This paper assesses the Knowledge, Awareness, and Perception (KAP) of Climate Change among the visitors of Mashar National Park, Hail, Saudi Arabia. Empirically, it has been established that climate change has an impact not only on the cultural and natural heritage but also on the visitor traffic patterns in national parks. The objectives guiding the study center on the identification of the level of knowledge and the investigation of the perception of park visitors regarding climate change. In the Hail Region, which is in the Kingdom of Saudi Arabia's north central region, the average temperature ranges from 39°F to 103°F and is infrequently lower than 31°F or higher than 108°F. This KAP research adopted quantitative methods using a questionnaire survey for data collection. A total of 120 park visitors were purposively sampled for the study. It was concluded that the visitors in Al-Mashar Park are not fully prepared to mitigate the impact of climate change even though Hail is undoubtedly experiencing climate variability. According to the study's findings, recommendations were made to maintain the park and provide opportunities for managing the park in a way that would allow it to better adapt to the effects of climate change, maintain effective resource management, and improve tourist satisfaction.